2021
DOI: 10.1037/dev0001207
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ distress and poor parenting during a COVID-19 lockdown: The buffering effects of partner support and cooperative coparenting.

Abstract: The COVID-19 pandemic is placing demands on parents that may amplify the risk of parents' distress and poor parenting. Leveraging a prepandemic study in New Zealand, the current research tested whether parents' psychological distress during a mandated lockdown predicts relative residual changes in poorer parenting and whether partner support and cooperative coparenting buffer this potentially detrimental effect. Participants included 362 parents; 310 were from the same family (155 dyads). Parents had completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 44 publications
2
76
0
Order By: Relevance
“…Findings from the German Family Panel study indicated that both men and women (N = 781 individuals) in marital/cohabiting relationships declined in relationship satisfaction from before to during the pandemic, regardless of pandemic-related employment changes [ 16 ]. Another study of 157 couples who were confined in mandatory quarantine with their children found that greater quarantine-related stress predicted residual decreases in relationship functioning (increased relationship problem severity, decreased problem-solving efficacy) and family functioning (increased home chaos, decreased family cohesion) [ 7 ], as well as residual increases in harsh parenting among those who perceived low (but not high) partner support [ 17 ].…”
Section: Loss Separation and Isolation And Relationship Outcomes (Pat...mentioning
confidence: 99%
“…Findings from the German Family Panel study indicated that both men and women (N = 781 individuals) in marital/cohabiting relationships declined in relationship satisfaction from before to during the pandemic, regardless of pandemic-related employment changes [ 16 ]. Another study of 157 couples who were confined in mandatory quarantine with their children found that greater quarantine-related stress predicted residual decreases in relationship functioning (increased relationship problem severity, decreased problem-solving efficacy) and family functioning (increased home chaos, decreased family cohesion) [ 7 ], as well as residual increases in harsh parenting among those who perceived low (but not high) partner support [ 17 ].…”
Section: Loss Separation and Isolation And Relationship Outcomes (Pat...mentioning
confidence: 99%
“…Thus, secure partners who enact effective buffering strategies (Table 2) within family contexts might create positive couple and family spillover processes by building cohesive, responsive and cooperative family environments that buttress both parents' and children's security and well-being. Moreover, parents' shared investment in caring for their children might lead insecure people to be more willing to rely on and trust partner support within co-parenting or family contexts compared with couple contexts [141][142][143] . If so, family interactions could be a powerful context in which partners can counteract the impact of attachment insecurity and generate positive spillover that bolsters attachment security.…”
Section: Co-parenting Interactions Following Couple Conflictmentioning
confidence: 99%
“…The contributions to this special issue indicate that the pandemic and the measures affected aimed to prevent the virus from spreading impacted families across different levels of the family system, such as: (a) changed family routines and rules (Bülow et al, 2021; Eales et al, 2021) and increased chaos (Cassinat et al, 2021) at the family level; (b) both positive (Donker et al, 2021) and negative (McRae et al, 2021) changes in the qualities of the caregiver-child relationship at the dyadic level; and (c) changes in the wellbeing of individual family members, as evidenced by increased worry, concern, sadness, and stress in caregivers (Eales et al, 2021) and higher levels of internalizing (Gadassi Polack et al, 2021) and externalizing problems (Skinner et al, 2021) in children and adolescents.…”
Section: The Impact Of the Covid-19 Pandemic On Families And Childrenmentioning
confidence: 99%
“…Families already experiencing more negative interactions before the pandemic tended to have more difficulties adjusting during the pandemic, possibly further accentuating difficulties between family members (Qu et al, 2021; Sun et al, 2021). At the same time, positive family functioning seemed to buffer against the effects of the pandemic (McRae et al, 2021; Skinner et al, 2021). These findings suggest that the pandemic disproportionally affects children, caregivers and families who are already at risk, either through limited resources at the relationship level, or through other well-known risk factors, such as low socioeconomic status and mental health vulnerabilities.…”
Section: Differential Impact Of the Covid-19 Pandemic On Families And...mentioning
confidence: 99%